Environmental impact of different agricultural production systems - Feitosa, Erialdo; Lopes, Fernando; Andrade, Eunice; Magalhães, Ana Caroline; Freitas, Cley Anderson (Revista Ciência Agronômica, 2021)
The efficient use of natural resources in production systems is essential for achieving ecological balance and sustainability in these systems. Current agricultural production systems have intensified the use of fertilisers and pesticides that contribute to an increase in energy flow, accelerating the process of degradation. The aim of this study was to evaluate, using emergy analysis, the environmental performance of different irrigated production systems for different sources of water, energy and fertiliser, and of rainfed systems under different types of soil preparation. The irrigated systems were studied in the experimental area of the Sewage Treatment Station (ETE) in Tianguá, Ceará (CE), and the rainfed models at the Fazenda Normal Farm in Quixeramobim, CE. Emergy analysis basically consists of three stages: construction of the systemic energy flow diagram, elaboration of the emergy evaluation table, and calculation of the emergy indicators. A mean value of 0.04 was found under the rainfed production systems, which shows less environmental stress compared to the irrigated systems, 0.30. The influx of economic resources into agricultural systems increases the environmental load and reduces renewability. Treated domestic effluent and photovoltaic solar energy afforded an increase in emergy yield and in the environmental sustainability of the production models.